Antioxidant for treatment of diabetic nephropathy: A systematic review and meta-analysis. (25th December 2017) - Kandhare, Amit D.; Mukherjee, Anwesha; Bodhankar, Subhash L.
Abstract: Background: Diabetic nephropathy (DN) is one of the leading causes of morbidity and mortality amongst the diabetes mellitus patients. Oxidative stress played a major role in the pathogenesis of DN. Many studies reported that therapies with antioxidant potential have a beneficial effect on DN but there is conflicting evidence amongst them. Objective: To elucidate the association between antioxidant and DN and to develop a robust evidence for clinical decisions by conducting systematic reviews and meta-analysis. Patient and methods: A comprehensive systematic literature search was conducted in PubMed, EMBASE, Cochrane Library, CPCI-S, ICTRP, and Google Scholar till February 2017 by two independent researchers. Various outcomes were included and statistical analyses were performed using RevMan V.5.3. Results: There were total 1461 participants identified from twelve studies, of which 882 (60.37%) were monitored on antioxidant treatment. Results indicated that antioxidant treatment was associated with significantly change in Blood Urea Nitrogen (SMD = 1.11, 95% CI: 0.38 to 1.85, p = 0.003), urinary Transforming Growth Factor-β (SMD = 2.16, 95% CI: -0.01 to 4.33; p = 0.05) and estimated Glomerular filtration Rate (SMD = 0.30, 95% CI: 0.06 to 0.55; p = 0.02) than control group. There was no association of change in urine albumin-to-creatinine ratio, serum creatinine, adverse events and rate of death with antioxidant treatment. Conclusion: The findings of this investigation indicate that antioxidant treatment is effective clinically for DN treatment in T2DM patient. However, there is a need of high degree of caution for interpreting the outcomes of the studies with a short duration of antioxidant treatment. Highlights: Objective was to elucidate the association between antioxidant and diabetic nephropathy (DN). Comprehensive systematic-literature search was conducted by two independent researchers. Antioxidant treatment was associated with significantly change in Blood Urea Nitrogen ( p = 0.003). It also associated with change in urinary TGF-β (SMD = 2.16, 95% CI: -0.01 to 4.33; p = 0.05). Antioxidant treatment is effective clinically for DN in Type-2 diabetes mellitus patient.